Heat transfer and fluid flow characteristics investigation using detached ribs in an axisymmetric impinging jet flow - Rasheed, Adnan; Allauddin, Usman; Ali, Hafiz Muhammad; Uzair, Muhammad; Verdin, Patrick G.; Siddiqui, Yasir H. (Springer, 2022)
This research work is directly concerned with the heat transfer involved in a single jet flow covering a heated surface having detached ribs present above the surface. A computational study has been conducted to check the effect due to the presence of such detached ribs. The generalized k−ω (GEKO) turbulence model with Reynolds-averaged Navier–Stokes equations formulation has been adopted after validation with the relevant experimental data from the literature. A rectangular rib design was selected for which rib width, height, clearance, pitch and first rib radial distance were varied to study their effect on heat transfer. Local heat transfer distributions were investigated over the target surface, especially focusing on the ribs-based region for different nozzle positions. The thermal performance with and without ribs is compared. A maximum increase in heat transfer of 64% was observed for a normalized nozzle to plate spacing z/d = 0.5.
Keywords: Jet impingement; Heat transfer enhancement; Detached ribs; GEKO turbulence model; Nusselt number